2008
DOI: 10.1354/vp.45-1-19
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of the Lichen Secondary Metabolite (+)-Usnic Acid in Domestic Sheep

Abstract: Abstract. Toxicity following ingestion of the vagrant, foliose lichen Xanthoparmelia chlorochroa was identified as the putative etiology in the death of an estimated 400-500 elk on the Red Rim-Daley Wildlife Habitat Management Area in Wyoming during the winter of 2004. A single, unsubstantiated report in 1939 attributed toxicity of X. chlorochroa in cattle and sheep to usnic acid, a common lichen secondary metabolite. To test the hypothesis that usnic acid is the proximate cause of death in animals poisoned by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 21 publications
0
33
0
1
Order By: Relevance
“…Other toxicity indices, such as serum lactate dehydrogenase, aspartate aminotransferase and creatine kinase, were also increased. A complete postmortem examination revealed that pathological changes occurred exclusively in the skeletal muscle (52). This is in sharp contrast with mice, rats, and humans, in which the liver is considered to be the most vulnerable organ with usnic acid insults.…”
Section: In Vivo Toxicity Datamentioning
confidence: 85%
See 2 more Smart Citations
“…Other toxicity indices, such as serum lactate dehydrogenase, aspartate aminotransferase and creatine kinase, were also increased. A complete postmortem examination revealed that pathological changes occurred exclusively in the skeletal muscle (52). This is in sharp contrast with mice, rats, and humans, in which the liver is considered to be the most vulnerable organ with usnic acid insults.…”
Section: In Vivo Toxicity Datamentioning
confidence: 85%
“…Unfortunately, there was no further information regarding usnic acid-induced toxicity described in the report (51). Feeding domestic sheep with usnic acid of 323-776 mg/kg for a maximum of 9 days induced several clinical signs such as lethargy and anorexia, or even death, with the estimated median toxic dose between 485 and 647 mg/kg (52). Other toxicity indices, such as serum lactate dehydrogenase, aspartate aminotransferase and creatine kinase, were also increased.…”
Section: In Vivo Toxicity Datamentioning
confidence: 97%
See 1 more Smart Citation
“…Serum chemistries and a complete blood cell count were conducted on all blood samples, as previously described. 6 Urine was collected from each ewe at least once while the animal was on a 100% lichen diet via metabolism cage. Upon collection, urine samples were immediately filtered a and subsequently refrigerated until urinalysis (typically within 6-24 hr).…”
Section: Sample Collectionmentioning
confidence: 99%
“…In a recent experimental study, however, administration of usnic acid orally did not duplicate the syndrome in domestic sheep. 6 Given the lack of information regarding X. chlorochroa toxicity, diagnosis is difficult, and treatment options are nonexistent. A combination of intravenous fluids; vitamins A, B, D, and E; selenium; calcium gluconate; dextrose phosphorus; magnesium; potassium; and anti-inflammatory and corticosteroid drugs had no beneficial effect in 4 symptomatic elk.…”
Section: Introductionmentioning
confidence: 99%